Cutting propagation of ‘Cambona 4’ yerba mate clones - Mayer, Leonardo; Nienow, Alexandre Augusto; Tres, Laura (Comunicata Scientiae, 2020)
The ‘Cambona 4’ yerba mate (Ilex paraguariensis A. St. Hil. - Aquifoliaceae) stands out for the high productivity and soft taste of the raw material obtained. The seedlings come from the controlled crosses of a female and a male plant. In order to guarantee the planting of even more uniform and productive herbs, the cutting is an alternative of propagation. The objective of this research was to evaluate the rooting capacity of apical and subapical cuttings of six ‘Cambona 4’ clones (C7, C8, C9, C10, C11 and C13) in two seasons, in january (summer/autumn) and april (autumn/winter) treated with 2.000 mg/kg of IBA in the form of talc. The cuttings were standardized with 10 cm, keeping a pair of leaves cut in half. The cutting was done in an agricultural greenhouse, with irrigation by intermittent nebulization, the cuttings were placed to rooting in plastic tubes containing carbonized rice husk. After 120 days, it was verified that the cutting season influenced the response of each clone, but for most clones rooting was higher when performed in summer/autumn, with better rates varying between 78.2% to 90.6% (C8, C9, C11 and C13), while in autumn/winter it was from 59.4% to 75.0% (C7, C10, C11 and C13). In the summer/autumn cutting period, subapical cuttings showed greater survival and rooting than the apical ones, but they didn’t differ when performed in autumn/winter. Leaf retention positively influenced the survival.